Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.14776/kjpid.2012.19.3.131
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Agents in Bacteremia of Children with Hemato-oncologic Diseases (2006-2010): A Single Center Study

Abstract: Purpose : This study was performed to identify the etiologic agents and antimicrobial susceptibility patterns of organisms responsible for bloodstream infections in pediatric cancer patients for guidance in empiric antimicrobial therapy. Methods : A 5-year retrospective study of pediatric hemato-oncologic patients with bacteremia in Seoul National University Children's Hospital, from 2006 to 2010 was conducted. Results : A total of 246 pathogens were isolated, of which 63.4% (n=156) were gram-negative, bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Among the GNB infections, the proportion of AR bacterial infections also tended to increase recently [ 2 7 8 10 19 20 21 ]. In Korean children with hematological/oncological disorders, GNB caused 49โˆ’62% of bacteremia cases in the 2000s, a higher proportion than in western children [ 22 23 24 ]. In the present study, 53.9% of bacteremia cases were caused by GNB, which was similar to the previous results in Korean children; however, it was higher than previously reported proportion of GNB, 41.8%, in our hospital in 2009.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the GNB infections, the proportion of AR bacterial infections also tended to increase recently [ 2 7 8 10 19 20 21 ]. In Korean children with hematological/oncological disorders, GNB caused 49โˆ’62% of bacteremia cases in the 2000s, a higher proportion than in western children [ 22 23 24 ]. In the present study, 53.9% of bacteremia cases were caused by GNB, which was similar to the previous results in Korean children; however, it was higher than previously reported proportion of GNB, 41.8%, in our hospital in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on Korean children with hematological/oncological disorders reported that 15โˆ’21% of bacteremia due to E. coli and Klebsiella spp. was caused by ESBL-producing strains and 71% of bacteremia due to A. baumannii was caused by CRAB [ 22 23 24 ]. In addition, 42โˆ’75% of bacteremia cases due to Enterococci were caused by VRE, 29โˆ’50% of bacteremia cases due to S. aureus were caused by MRSA, and 82โˆ’87% of bacteremia cases due to CNS were caused by MRCNS [ 22 23 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, children with potential immunocompromised status are known to have blood stream infection from coagulase negative Staphylococcus [2,3,4]. Korean studies have shown that among Gram-positive organisms, coagulase negative Staphylococcus and viridans group Streptococcus are most frequently isolated from immunocompromised pediatric blood cultures [5,6]. These findings are of interest.…”
Section: Introductionmentioning
confidence: 99%